Hubungan Citra Diri dan Hubungan Sosial Antar Kelompok Sebaya dengan Tingkat Kepercayaan Diri pada Remaja di SMAN 1 Cilaku-Cianjur Tahun 2022 - Lathifa Siti Maulida; Mustopa Mustopa; Sanca Stella (Universitas Katolik Widya Karya Malang, 2023)
Self-image is a description or assessment of each individual's self, both in terms of knowledge and physical aspects. Meanwhile, social relationships are relationships between people who need each other and have a reciprocal relationship. The research objective is to determine the relationship between self-image and social relationships between peers on the level of self-confidence at SMAN 1 Cilaku-Cianjur. This type of research uses a quantitative descriptive research design with a cross sectional approach. Population and sample of students in grades 10 and 11. The sampling technique is: simple random sampling. The results and discussion concluded: 1. The results of the research found that there is an influence of Self Image. 2. The results of the research found that the influence of social relationships was that most of the respondents, 29 (61.7%) had moderate social relationships and some of the respondents, 18 (38.3%). ) have high emotional regulation skills in social relations. 3. The results of the study found that the self-confidence of the majority of respondents as many as 43 (91.5%) had moderate self-confidence and some respondents as many as 3 (6.4%) had high self-confidence and 1 (2.1%) of the respondents had low self-confidence. 4. There is an influence of self-image on self-confidence among teenagers at SMAN 1 Cilaku. 5. There is an influence of social relationships on self-confidence among teenagers at SMAN 1 Cilaku. 6 .Based on the results of research that has been carried out, the results of this hypothesis are accepted as showing that there is a relationship between self-image (X1) and social relationships (X2) on self-confidence (Y).